Interventions addressing the impostor phenomenon: a scoping review - Para, Emma; Dubreuil, Philippe; Miquelon, Paule; Martin-Krumm, Charles (Frontiers in Psychology, 2024)
Introduction The Impostor Phenomenon (IP) refers to a psychological experience characterized by unjustified feelings of intellectual and professional fraud, accompanied by the fear of not maintaining performance and of being exposed. IP is receiving increasing attention in the fields of psychological health at work and occupational psychology as well as among the general public, since it affects the functioning of both individuals and organizations. The aim of this scoping review is to map the range of interventions that have been conducted to address IP among individuals experiencing it in a professional context. Methods The search and selection process to identify relevant reports was conducted using the PRISMA-ScR methodology and JBI recommendations and resulted in the selection of 31 studies. Results The results reported concerning the characteristics of the studies, the interventions described, and the effects identified are heterogeneous. More than half of the studies used research designs (experimental, pre-experimental, exploratory, etc.). Two major types of intervention emerge: training and counseling. The effectiveness of the interventions varies according to the evaluation methodology that was used, although most authors conclude that the proposed intervention is relevant. Discussion In light of these results, recognizing and educating individuals regarding the various manifestations of IP, as well as offering support in a group context, appear to be primary intervention levers. Future intervention proposals should explore psychosocial and educational influences as well as the impact of the immediate environment on IP-related beliefs.